HEAD CT SCAN EXAMINATION PROCEDURE IN MENINGIOMA CASES IN THE RADIOLOGY UNIT OF AWAL BROS HOSPITAL, PEKANBARU - Wahyu Saputra; Putri Salsabilla (Medical Imaging and Radiation Protection Research Journal, 2024)
Background: Meningioma is an intracranial tumor that originates from meningeal cells and generally has a slow growth. Computed Tomography (CT) Scan of the head plays a role in helping assess the location, size, characteristics of the lesion, and the relationship of the tumor to surrounding structures. The use of contrast material can improve visualization of the boundaries and characteristics of the mass, thus aiding the diagnosis process. This study aims to determine the procedure for CT Scan of the head with contrast material in meningioma cases in the Radiology Unit of Awal Bros Hospital, Pekanbaru. Methods: The study used a qualitative method with a case study approach. Data collection was conducted in November 2023 through observation, interviews, and documentation. The research informants consisted of three radiographers, one radiologist, and one patient. Results: The examination began with preparation of equipment and patient, examination of urea and creatinine, providing informed consent, removal of metal objects in the head area, and positioning the patient supine with the head first entering the gantry. The examination was performed through a plain head scan and continued with an examination with iopamiro contrast material using an injector. The scan results were reconstructed in axial, coronal, and sagittal sections as needed. The case examination revealed a hypodense mass with multiple hyperdense lesions measuring approximately 6.5 × 6.3 × 7.6 cm in the bilateral frontal region. Contrast enhancement enhanced the tumor boundaries. Conclusion: The head CT scan procedure with contrast for meningioma includes patient preparation, laboratory tests, plain scanning, contrast administration, contrast scanning, and image reconstruction. Contrast enhancement helps clarify the boundaries and characteristics of the meningioma mass, thus supporting the diagnostic evaluation.